Evaluation of the Prevalence of Drug Abuse and Smoking in Parents of ‎Children with Attention Deficit Hyperactivity Disorder - Nooshin Parvaresh; Shahrzad Mazhari; Neda Mohamadi; Najmeh Mohamadi (Addiction and Health, 2015)
Background: Attention deficit hyperactivity disorder (ADHD) affects 5% of children. In addition to pharmacotherapy, non-drug treatments such as appropriate parenting are also very important in the treatment of these children. Diagnosis and treatment of parents with psychiatric disorders and substance abuse and evaluation of the frequency of these disorders in parents is critical. Methods: In this case-control study, 200 parents were studied. The target population included parents of 7 to 12 year-old children who referred to child and adolescent psychiatric clinics. The control group included parents of children who referred to child non-psychiatric clinics. The parents were evaluated via a demographic information form, and structured interviews based on the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV) for nicotine and drug addiction. Then, the Hamilton Anxiety Rating Scale (HAM-A) and Hamilton Depression Rating Scale (HDRS) was used to assess their anxiety and depression. Findings: Among the studied parents, the comparison of drug abuse, smoking, and stress showed significant differences between the two groups. In terms of depression and ADHD, the difference between the case and control groups was not statistically significant. Conclusion: The higher prevalence of these disorders in parents of children with ADHD may indicate the possible role of this disorder in the etiology.